(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
In accordance with the trends of innovative development in the field of education in the world, special attention is paid to the improvement of the pre-school education system based on competency requirements. In particular, organization of high-quality educational services aimed at developing independent and creative thinking in children for the purposes of sustainable development set by UNESCO until 2030 has been noted as an urgent task. International experiences create the need to increase the effectiveness of the pedagogical process in preschool educational institutions, to introduce the basics of STEAM education from an early age, and to differentiate educational services.